Protection of Thiophenone in Catfish (Clarias sp.) Larvae When Challenged with Aeromonas hydrophila - Indriyanti, Ana; Julyantoro, Pande Gde Sasmita; Wijayanti, Ni Putu Putri (Advances in Tropical Biodiversity and Environmental Sciences; Vol 5 No 1 (2021): ATBES, 2021)
This research aimed to determine the ability of quorum sensing inhibitor compound thiophenone to protect catfish ( Clarias sp.) larvae when challenged with the pathogenic Aeromonas hydrophila . This research was conducted at Fisheries Laboratory, Faculty of Marine Science and Fisheries, Udayana University, from December 2019 to January 2020. The experiment was setting up with four treatments and three replications for each treatment. 10 larvae of catfish were maintained in aquarium 15 cm × 15 cm × 20 cm filled with 1 liter of freshwater and used aeration for oxygen supply. The treatments were treatment A (control), treatment B (addition of A. hydrophila 10 6 cfu/ml), treatment C (addition of thiophenone 10 µM), and treatment D (addition of A. hydrophila 10 6 cfu/ml and thiophenone 10 µM). The results showed that the addition of thiophenone 10 µM increased the survival of catfish larvae up to 73% when challenged with A. hydrophila . That was significantly difference ( P <0,05) compare to treatment B with survival rate of 43% within 3 days of culture period. Although it was not statistically different ( P >0,05), the highest absolute weight and length were found in treatment A of 0,47 g and 0,50 cm, respectively, while the lowest absolute weight and length were found in treatment B about 0,23 g and 0,17 cm, respectively. The water quality such as temperature, pH and DO were still within the range that supported the growth and survival of catfish larvae during this study.